2006
DOI: 10.1359/jbmr.060307
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D–Resistant Rickets and Type 1 Diabetes in a Child With Compound Heterozygous Mutations of the Vitamin D Receptor (L263R and R391S): Dissociated Responses of the CYP-24 and rel-B Promoters to 1,25-Dihydroxyvitamin D3

Abstract: We report here the first association between vitamin D-resistant rickets, alopecia, and type 1 diabetes in a child with compound heterozygous mutations in the VDR gene. Transfection studies suggest dissociated effects of VDR gene mutations on the regulation of genes involved in vitamin D metabolism and dendritic cell maturation.Introduction: Whereas vitamin D may play a role in the immune tolerance process, no patient has been reported to associate hereditary vitamin D-resistant rickets (HVDRR) and an autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 39 publications
(80 reference statements)
0
28
0
Order By: Relevance
“…The importance of this residue on the dimerization process with retinoid X receptor alpha (RXRA) was previously shown with an artificial p.Arg415Ala mutant, which resulted in a complete loss of function (Shulman et al, 2004). In addition, this position is homologous to p.Arg391Cys/Ser mutations in vitamin D receptor (VDR) (Figure 2), which have been shown to cause vitamin D-resistant rickets by destabilizing the dimerization with RXRA (Nguyen et al, 2006;Whitfield et al, 1996). To evaluate whether the LXRA p.Arg415Gln mutation has a similar detrimental effect on the dimerization with RXRA, we performed binding assays with wildtype and mutant LXRA.…”
Section: Dimerization Analysis and Transcriptional Regulation Of Nr1hmentioning
confidence: 90%
“…The importance of this residue on the dimerization process with retinoid X receptor alpha (RXRA) was previously shown with an artificial p.Arg415Ala mutant, which resulted in a complete loss of function (Shulman et al, 2004). In addition, this position is homologous to p.Arg391Cys/Ser mutations in vitamin D receptor (VDR) (Figure 2), which have been shown to cause vitamin D-resistant rickets by destabilizing the dimerization with RXRA (Nguyen et al, 2006;Whitfield et al, 1996). To evaluate whether the LXRA p.Arg415Gln mutation has a similar detrimental effect on the dimerization with RXRA, we performed binding assays with wildtype and mutant LXRA.…”
Section: Dimerization Analysis and Transcriptional Regulation Of Nr1hmentioning
confidence: 90%
“…(14,15) In addition to this case, two other cases of HVDRR were shown to be caused by compound heterozygous mutations in the VDR. (4,16) Both patients also had alopecia. One patient had two missense mutations in the VDR LBD that resulted in L263R and R391S amino acid substitutions.…”
mentioning
confidence: 96%
“…One patient had two missense mutations in the VDR LBD that resulted in L263R and R391S amino acid substitutions. (16) The second patient had a single base deletion in exon 4 that led to a frameshift and downstream termination codon in exon 4 and a missense mutation in the VDR LBD that resulted in an E329K amino acid substitution. (4) The clinical case had some slightly unusual features.…”
mentioning
confidence: 99%
“…Indeed, functional analyses of mutated VDR LBD have shown that defects in this protein region may affect adequate protein expression, the heterodimerization process or the VDR affinity to ligand or coactivators. Alopecia has been suggested to be associated with mutations in LBD subregions which are essential for the heterodimerization with RXR [7,18,21,22,23] and is generally related to severe hormone resistance [1]. Furthermore, treatments may correct the serum biochemical profile and heal the rickets, with no significant change in the hair development.…”
Section: Discussionmentioning
confidence: 99%